How Integrated Management Strategies Promote Protein Quality of Cotton Embryos: High Levels of Soil Available N, N Assimilation and Protein Accumulation Rate - Yang, HongKun; Meng, YaLi; Chen, BingLin; Zhang, XingYue; Wang, YouHua; Zhao, WenQing; Zhou, ZhiGuo (Frontiers in Plant Science, 2016)
Cottonseed is widely used as a source of ruminant feed and for industrial purposes. Therefore, there is a tremendous need to improve the nutritional value of cotton embryos. In this study, a conventional management (CM) and two integrated cotton management strategies (IMS1, IMS2) were performed at two soil fertility levels to study the relationships among soil N, N assimilation, embryonic protein accumulation and protein quality. The levels of proteins, essential amino acids, and semi-essential amino acids, especially those of glutamate, lysine, and methionine, were higher in IMS1 and IMS2 embryos than in CM embryos. These changes were significantly positively correlated with the soil-available N content, glutamine synthetase (GS) activity and peak value of protein accumulation rate and were negatively correlated with the free amino acid level. These results illustrated that integrated management strategies, especially the rates and timing of N application, raise the level of soil available N, which is beneficial for N assimilation in developing cotton embryos. The protein content was limited by the rate of protein accumulation rather than by the free amino acid content. The combination of target yield fertilization, a growth-driven N application schedule, a high plant density and the seedling raising with bio-organic fertilizer can substantially improve protein quality in cotton embryos, especially at a soil with low soil organic matter and total nitrogen.